Astronomy for Precise Positioning and Stellarium - Gurung, Sher Bahadur; Musyaju, Satish (Cognition, 2022)
Astronomy studies the Universe as a whole. Astronomy is the science that studies the origin and evolution of the Universe and everything in it. The present study discussed on the application of astronomy in general and explored its application on precise positioning specifically. Calendars, computers, communication satellites, navigation systems, mathematics, trigonometry, solar panels, wireless internet, culture and religions, and many other technological applications development such as aerospace, Global Navigation Satellite System (GNSS) or precise positioning, solar and nuclear energy, medicine, and many other technological applications development are all examples of astronomy. The study is conducted based on secondary information and astronomical observation using virtual application software. This paper also introduced the astronomical application software stellarium. The study shows that the astronomical knowledge and techniques are very useful for precise positioning.